A model and a numerical scheme to compute laminar flames in dust suspensions - D'Amico, Donato; Dufaud, Olivier; Grapsas, Dionysios; Latché, Jean-Claude (Proceedings of the Conference Algoritmy, 2016)
We address in this paper a system of balance equations which models the low Mach number one-dimensional reactive flow generated by the combustion of a dust suspension. This model features rather general diffusion terms, with, in particular, mass diffusion coefficients which depend on the local composition and differ in function of the considered chemical species. For the solution of this system, we develop a fractional step finite volume algorithm which preserves by construction the stability properties of the continuous problem, namely the positivity of the chemical species mass fractions, the fact that they sum is equal to one, and the non-decrease of the temperature, provided that the chemical reaction is exothermic.